Socioprofessional dimension of teacher training: theoretical contributions and proposals - Sarti, Flavia Medeiros (2019)
The present article focuses on the socioprofessional dimension of teacher training, based on assumptions linked to the Sociology of Practice and the Sociology of Knowledge. It centers on the concepts of habitus and of geração, taking them as unifying principles of teaching practice and proposing to articulate them with precepts of professional teacher development. The discussion is supported by a review of the literature on the processes involved in the learning and professional development of teachers. It concludes that professional teacher training at the university level requires alternating between the school and the involvement of multiple categories of trainers in which experienced teachers have a place, including in the formative monitoring of future teachers.